Potencial citotóxico e virulência de Enterococcus sp. isolados de ambiente aquático - Mikalouski, Udson (2017)
Enterococcus spp. belong to the group of lactic bacteria and are present in soils, waters, plants, autochthonous microbiota of various foods and as members of the intestinal microbiota of animals and animals. These microorganisms have been observed as commensals for a long time, but the increased of severity nosocomial infections caused by multi-resistant antimicrobial enterococci and a lack of knowledge about their virulence factors generate insecurity for public health. Our study aimed to evaluate the cytotoxic capacity, resistance and virulence of Enterococcus sp. that comes from aquatic environments. It was studied resistence genes to AVancomycin (vanA and vanB) and virulence as gelatine production (gelE), collagen adhesion of Enterococcus (ace), bacteriocins cytolysin-activating (cylA), endopeptidase serine (sprE), and pathogenicity islands (PAI), aggregation substance (asa1), sexual pheromone (cpd), agglutination substance (agg) and phenotypic test of resistance to antibiotics, cytotoxicity in HeLa cells and biofilm formation. All the isolates presented biofilm capacity and cytotoxic potential with different intensities, and 66.66% of the isolates presented resistance to vancomycin and 58% to ampicillin. An E. casseliflavus isolate shows resistance to all antibiotics tested, as well as biofilm formation and cytotoxic potential. The species of Enterococcus sp. analyzed presented independent characteristics, which reinforce the importance of studies in the most varied environments.